Knowledge, Attitude and Perception of Undergraduate Health Science Students towards Complementary and Alternative Medicine: A Cross-Sectional Study in Nepal - Poudel, Melina; Pandit, Manoj; Shrivastava, Amit Kumar; Chhetri, Anjana Paudel; Pandey, Deepesh; Pandey, Bipindra; Koirala, Hem Raj; Karki, Dipesh; Sharma, Saroj; Koirala, Niranjan (Annapurna Journal of Health Sciences, 2023)
Introduction: Apparently, Complementary and Alternative Medicine (CAM) is a recognized medical practice that precisely makes use of multiple treatment therapies and techniques in the prevention and management of variety of human disorders. Having a glance at the future, health science students belonging to different universities would take the leading hospitals and health centers thus this study aims to analyze the level of knowledge, attitude and perception of them towards CAM in Nepal, also aims at awaking students about CAM therapies, related side effects, risks and possible complications. Methods: A cross sectional descriptive study was organized by enlisting 385 undergraduate students, pharmacy (107) and non-pharmacy (278) which encompasses demographic characteristics, source of information, knowledge, attitudes and perception towards CAM. Results: Report indicated that predominance of students had good knowledge regarding homeopathy (Pharmacy:81.3%, NP:71.9%, P-value:0.044), herbal-medicine (Pharmacy: 62.5%, NP: 56.5%, P-value: 0.008, acupuncture (Pharmacy: 72.9%, Non-Pharmacy: 62.2%, P-value: 0.073), gingko (Pharmacy: 52.3%, Non-Pharmacy: 40.6%), ginseng (Pharmacy: 52.3, Non-Pharmacy: 34.9%, P-value: 0.001). In spite employing non reliable origin of CAM information and their mindset that CAM is proceeded by quacks, the preponderance of students had positive attitudes and perception regarding CAM management. However, few non pharmacy students believe that CAM should be adapted by legislation (Pharmacy: 78.5%, Non-Pharmacy: 66.2%, P-value: 0.032), only few believe that CAM is a convenient appendage via traditional medication (Pharmacy: 84.1%, Non-Pharmacy: 70.5%, P-value: 0.018). Conclusion: Disregarding scanty knowledge in the matter of CAM, students possess forward-looking attitudes and opinion regarding CAM, also express eagerness to increase their knowledge about CAM.